Assessing the risks of abuse of opioids in real-world data - M. V. Pchelintsev (Реальная клиническая практика: данные и доказательства, 2023)
In the review, data from foreign medical publications are presented, which are dedicated to the narcogenic potential of a strong opioid. Risk assessments of drug addiction development, of its diversification into illegal trafficking for non-medical use are given. Assessment data have a comparative character with opioids. In analyzed articles, the authors used different methodological approaches to the assessment of strong opioids narcogenicity, in particular to the evaluation of the results of population-based cohort studies, to the analysis of large databases accumulating data on different drug abuse, including opioids, data on intoxication with preparations of the group, and some others. Based on the analysis of published assessment results of potential risks of strong opioids use, the author gives the evaluation of the organization of its accountability and prescription in the Russian Federation.